Student team achievement division model assisted by card media in social studies learning - Sulfemi, Wahyu Bagja (Universitas Negeri Malang, 2023)
The research aims to see how far the use of the STAD model assisted by card media improves learning outcomes and students' activeness and interest in learning. The method used was remedial action or classroom action research. The subjects were teachers and fifth-grade students at Pasirgunung Selatan 4 Elementary School, Depok, totaling 38 participants. The learning outcomes of the first cycle using the discussion method obtained an average of 69 (58 percent mastery learning) and 25 (66 percent) who actively answered. Cycle 2 using the STAD Model assisted by card media obtained an average of 80, completeness reached 80 percent, and student activity was 32 (84 percent). The results of the study can be concluded that STAD model assisted by by card media increases the class average value, learning completeness, student learning outcomes, student activities, and growth the cohesiveness and student interaction. The use of the STAD model assisted by card media has implications for social studies learning such as resulting data that makes it easy to measure students’ learning outcomes through comparisons between understanding before and after use. In addition, this research has the potential to enhance students' interaction and understanding of complex materials in social studies, as well as develop social and cognitive skills that are important for their development.